Situational judgment testing: A review and some new developments - OOSTROM, Janneke K. (Institutional Knowledge at Singapore Management University, 2015)
Although situational judgment tests (SJTs) have a long history in the personnel selection literature, there have been some recent developments in how they are designed, administered, and scored. An SJT is a measurement method typically composed of challenging work-related situations and a list of plausible courses of action. Test takers are asked to evaluate each course of action for either the likelihood that they would perform the action or the effectiveness of the action. In this book chapter, we first briefly review current practice regarding the development of SJTs in personnel selection. We also review evidence concerning reliability, construct-related validity, criterion-related validity, subgroup differences, fakability, and acceptability by test takers. Then, we focus on several promising new developments regarding the way SJTs are designed and scored. The chapter concludes with a list of areas that need to be addressed in future research.